The Effect of Complex Exercises in Different Shapes and Spaces to Develop Some Special Physical Abilities and the Velocity of the Skillful Performance of Football Players - Hussein Habib Mosleh (Journal of Global Pharma Technology, 2018)
The problem of research is the amount of weakness in the level of some physical abilities, which has a negative impact on the low level of skill performance and shows through random play and slow movement within the stadium and the large number of cases cut in performance. Objectives There are statistically significant differences between the results of the post and remote tests of the two research groups in the search variables and in favor of the post tests. There are also significant differences between the control and experimental research groups in the remote tests and in favor of the experimental group. The experimental method was used for the nature of the research problem. The sample consisted of (48) players distributed to 22 control groups (22) for the experimental group and they represent the Soran Club. The experimental method of the experimental group in the experimental curriculum has developed in some special physical abilities and the velocity of the skillful performance of the research sample. The most important recommendations are to adopt the training method in specific areas and in different forms in the training curricula in the preparation and special stages.Keywords: Complex exercises, Physical abilities, Velocity and skillful performance.